Vocational education as a tool to develop ninth graders’ oral communication in english. (2024)
This research explores the efficacy of Problem-Based Learning (PBL) and roleplay techniques in fostering deeper engagement and enhancing oral communication skills among ninth-grade female students within the context of Vocational Education. The study investigates how these pedagogical tools contribute to students' self-recognition in personal and social terms, their vocational orientation, public speaking skills, and various English language aspects. Through a mixed methods approach, including surveys, interviews, and classroom observations, data was collected and analyzed to understand the impact of PBL and roleplay on students' empowerment and overall educational outcomes. Results indicate a significant positive correlation between the implementation of PBL and roleplay strategies and students' enhanced engagement with Vocational Orientation, oral communication skills, and self-perception in both personal and vocational contexts.